VARIASI LEKSIKAL BAHASA WAKATOBI: KAJIAN DIALEKTOLOGI (Lexical Variation of the Wakatobi Language: Dialectology Study) - Taembo, Maulid (Kandai, 2023)
The Wakatobi language variations are still a subject of interesting discussion and debate, not only among language researchers, but also among the people of Wakatobi. Previous studies that have different conclusions encourage wide discussions and studies on the diversity of Wakatobi languages. This study provides an overview and concrete manifestation of this variation, especially regarding the lexical variation of the Wakatobi language. Data collection was done by interview and observation methods. The tabulated data were analyzed descriptively qualitatively using traditional dialectology theory. The results of the research show that all fields of meaning consisting of several glosses provide an overview of lexical variations at several observation points. Almost all the compared lexicons show a grouping of language variations, which were observed from different islands. This study concludes that there are four major variations (isolects) of the Wakatobi language, namely the language variations spoken on Wangiwangi, Kaledupa, Tomia, and Binongko Islands. However, not all lexicons differ from these variations (isolects). There are isolects that have the same lexicons as other isolects, such as the gloss ‘mole’, for the Waha, Mandati Lia, and Kapota areas, are not different from the Kaledupa area, but different from the Tomia area and also different from the Binongko area. Variasi bahasa Wakatobi masih menjadi bahan diskusi dan perdebatan yang menarik, tidak hanya di kalangan peneliti bahasa, melainkan juga di kalangan masyarakat Wakatobi. Penelitian terdahulu yang menghasilkan kesimpulan yang berbeda membuka lebar diskusi dan kajian kebervariasian bahasa Wakatobi. Penelitian ini memberikan gambaran dan wujud nyata adanya kebervariasian tersebut, khususnya terkait variasi leksikal bahasa Wakatobi. Penyediaan data dilakukan dengan metode cakap dan metode simak. Data yang telah ditabulasi dianalisis secara deskriptif kualitatif menggunakan teori dialektologi tradisional. Hasil penelitian menunjukkan bahwa semua medan makna yang terdiri atas beberapa glos memberikan gambaran variasi leksikal di beberapa titik pengamatan. Hampir semua berian yang dibandingkan memperlihatkan adanya pengelompokan variasi bahasa, yang diamati dari pulau yang berbeda. Kajian ini menyimpulkan bahwa ada empat variasi (isolek) besar bahasa Wakatobi, yaitu variasi bahasa Wakatobi yang dituturkan di Pulau Wangiwangi, Kaledupa, Tomia, dan Binongko. Namun demikian, tidak semua berian berbeda dari semua variasi (isolek) tersebut. Ada isolek yang memiliki berian yang sama dengan isolek lainnya, seperti glos ‘tahi lalat’, wilayah Waha, Mandati Lia, Kapota, tidak berbeda dengan wilayah Kaledupa, tetapi berbeda dengan wilayah Tomia dan juga berbeda dengan wilayah Binongko.